Application of Autofluorescence for Analysis of Medicinal Plants. (26th November 2017) - Roshchina, Victoria V.; Kuchin, Andrei V.; Yashin, Valerii A.
Abstract : Autofluorescence of secondary compounds contained in plant secretory cells may be applied to the analysis of medicinal plants for pharmacy. Emission and prevailing fluorescent pharmaceuticals have been estimated in several models of species such as Salvia officinalis, Berberis vulgaris, Humulus lupulus, and Matricaria chamomilla, by luminescence microscopy, microspectrofluorimetry, and confocal microscopy.